Direct Differentiation of Human Embryonic Stem Cells toward Osteoblasts and Chondrocytes through an Intermediate Mesenchyme Progenitor Lineage - Abdallah, Basem M.; Harkness, Linda; Mahmood, Amer; Kassem, Moustapha (IntechOpen, 2011)
None